Accelerated polaron formation in perovskite quantum dots monitored via picosecond infrared spectroscopy. Issue 10 (24th February 2023) - Nuber, Matthias; Tan, Qi Ying; Sandner, Daniel; Yin, Jun; Kienberger, Reinhard; Soci, Cesare; Iglev, Hristo
Abstract : Picosecond mIR-spectroscopy reveals polaron stabilization processes in perovskite quantum dots on a few ps time-scale, considerably faster than the bulk analogue. Abstract : The formation and nature of polarons in perovskite quantum dots (QDs) are still unclear. Due to the very limited crystal size and quantum confinement, influences on the polaron stabilization dynamics could be expected. Here, we investigate the coupling of photoexcited charges to vibrational modes in mixed cation lead halide Cs0.2 FA0.8 PbBr3 QDs via picosecond mid-infrared spectroscopy in comparison to the bulk film. We find additional processes occurring in an infrared activated vibrational (IRAV) mode compared to the ground-state bleaching and screened carrier background signal. Using that mode as a proxy for the charge-molecular bond coupling, we interpret additional time constant as a polaron stabilization time. With the confinement effects present in the QDs, this time shortens from tens of picoseconds in the bulk to only a few picoseconds.